Comparison of Two Distraction Devices for Assessment of Passive Hip Laxity in Dogs - Santana, Ana; Alves-Pimenta, Sofia; Martins, João; Colaço, Bruno; Ginja, Mário (Frontiers in Veterinary Science, 2020)
Canine hip dysplasia is the most common orthopedic developmental condition in the dog and early hip laxity is the main risk factor. The importance of hip laxity in young animals in the development of hip dysplasia is unanimously recognized among researchers and veterinarians due to its medical applicability in terms of disease control and prevention. In the market, there is some certified hip distractors to promote joint laxity. However, the clinical use of some of these distractors complies with a set of usage rules, that can limit its medical application. In this study was compared the technical quality of radiographs and hip distraction using a certified hip distractor (CertD) and Dis-UTAD in 104 dogs (208 joints). The mean pelvic tilting of 1.5 ± 1.6° and 1.5 ± 1.8° were similar when using the CertD and the Dis-UTAD distractors, respectively (P > 0.05). In the CertD sample, the mean hip distraction index (DI) was 0.46 ± 0.17 and in the Dis-UTAD 0.46 ± 0.16; the mean DI differences was 0.001 ± 0.045, resulting in a non-significant paired t-test (P = 0.65) and a significant intraclass correlation coefficient of 0.96, with the 95% lower limit confidence interval of 0.95 (P < 0.05). The statistical power analysis showed a very low distraction index difference effect size. The results suggest that the statistical reproducibility of CertD hip distraction by the Dis-UTAD and the DI mean differences of 0.001 might be considered without clinical importance. The Dis-UTAD might be considered adequate to promote dog hip laxity.